(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: This study aimed to identify the modified impact of governance on the relationship between external electronic auditing and internal auditing tasks in commercial banks in Iraq. out of (386) male and female employees in the internal audit departments; Arithmetic means, standard deviation, simple and hierarchical regression analysis were used to test the hypotheses, and the study found a set of results, most notably: the existence of an effect of external electronic auditing on internal auditing tasks in commercial banks in Iraq, and the existence of an effect on governance as a modified variable in improving the relationship between external electronic auditing and the tasks of external auditing. Internal auditing in commercial banks in Iraq The study recommended a set of recommendations, the mo-st prominent of which are: The need for commercial banks in Iraq to provide information related to financial disclosure to shareholders and investors.